Effects of poly (ε-caprolactone) coating on the properties of three-dimensional printed porous structures. (June 2017) - Zhou, Zuoxin; Cunningham, Eoin; Lennon, Alex; McCarthy, Helen O.; Buchanan, Fraser; Clarke, Susan A.; Dunne, Nicholas
Abstract: Powder-based inkjet three-dimensional printing (3DP) to fabricate pre-designed 3D structures has drawn increasing attention. However there are intrinsic limitations associated with 3DP technology due to the weak bonding within the printed structure, which significantly compromises its mechanical integrity. In this study, calcium sulphate ceramic structures demonstrating a porous architecture were manufactured using 3DP technology and subsequently post-processed with a poly (ε-caprolactone) (PCL) coating. PCL concentration, immersion time, and number of coating layers were the principal parameters investigated and improvement in compressive properties was the measure of success. Interparticle spacing within the 3DP structures were successfully filled with PCL material. Consequently the compressive properties, wettability, morphology, and in vitro resorption behaviour of 3DP components were significantly augmented. The average compressive strength, Young׳s modulus, and toughness increased 217%, 250%, and 315%, following PCL coating. Addition of a PCL surface coating provided long-term structural support to the host ceramic material, extending the resorption period from less than 7 days to a minimum of 56 days. This study has demonstrated that application of a PCL coating onto a ceramic 3DP structure was a highly effective approach to addressing some of the limitations of 3DP manufacturing and allows this advanced technology to be potentially used in a wider range of applications. Graphical abstract: Highlights: Critical evaluation of PCL coating as post-process method to augment 3DP scaffold. Interparticle spacing within the 3DP scaffold was successfully filled with PCL. PCL coating extended long-term mechanical stability and bioresorption profile. Identified key coating factors affecting mechanical and bioresorption properties. PCL-CaSO4 scaffold could provide mechanical support to adjacent tissue in vivo.